Proceedings of the Second Italian Conference on Computational Linguistics CLiC-it 2015 - Cristina Bosco, Sara Tonelli, Fabio Massimo Zanzotto (dir.) (Accademia University Press, 2015)
CLiC-it 2015 is held in Trento on December 3-4 2015, hosted and locally organized by Fondazione Bruno Kessler (FBK), one the most important Italian research centers for what concerns CL. The organization of the conference is the result of a fruitful conjoint effort of different research groups (Università di Torino, Università di Roma Tor Vergata and FBK) showing the nationwide spreading of CL in Italy. As in the first edition, the main aim of the event is at establishing a reference forum on...